Dynamics of the activated state of NAD-dependent dehydrogenase investigated by a weighted histogram analysis semi-empirical method - de Souza, João C. P. [UNESP]; Silva, Wanderson O.; Freitas, Luis P. M. [UNESP]; Colombo, Rafael N. P.; Iost, Rodrigo M.; Feliciano, Gustavo T. [UNESP]; Lima, Fábio H. B.; Crespilho, Frank N. (Royal Society of Chemistry (RSC), 2024)
The complex interplay of structural dynamics and multi-pathway catalytic activity within a redox enzyme's active site has posed significant challenges for researchers seeking to comprehend the underlying mechanisms. This is especially evident in the case of NAD-dependent alcohol dehydrogenase (ADH) during ethanol oxidation. Despite continuous efforts since 1962, this complex enzymatic process has remained unresolved, indicating the highly difficult and elusive nature of the enzymatic reaction. Previous studies proposed structural modifications with the potential to enhance oxidation kinetics. However, the absence of experimental evidence left the nature and significance of these changes uncertain. To address this knowledge gap, we propose an approach named weighted histogram analysis semi-empirical method (WHA-SEM). This approach aims to map the potential energy surface and explore energy curve bifurcation within the framework of transition state theory. The method combines experimental protein film electrochemistry, differential electrochemical mass spectrometry (DEMS), and molecular dynamics simulations to elucidate the real-time dynamics of the catalytic enzymatic center. Our findings reveal that changes in ADH kinetics are not solely attributed to structural alterations. Instead, WHA-SEM identifies a shift in the underlying mechanism triggered by the high activation energy associated with the NAD+/NADH dissociation step. This energetic barrier significantly influences the overall catalytic efficiency of ADH. WHA-SEM highlights the interaction between ADH and acetaldehyde, which involves ion-dipole interactions facilitated by the carbonyl group. In contrast, the interaction with NADH engages a specific hydrogen bond network. Acetaldehyde interacts with nearby water molecules close to the pocket entrance of ADH, effectively reducing the energy required for its dissociation from the protein. The dissociation of NADH from ADH disrupts the hydrogen bond network, ultimately leading to the shielding of the charged NADH with water molecules.